Escherichia coli Nissle 1917 protects gnotobiotic pigs against human rotavirus by modulating pDC and NK‐cell responses. Issue 10 (11th August 2016) - Vlasova, Anastasia N.; Shao, Lulu; Kandasamy, Sukumar; Fischer, David D.; Rauf, Abdul; Langel, Stephanie N.; Chattha, Kuldeep S.; Kumar, Anand; Huang, Huang‐Chi; Rajashekara, Gireesh; Saif, Linda J.
Abstract : Mechanistic understanding of individual and interactive immunomodulatory and anti‐infectious effects of gram‐positive ( Lactobacillus rhamnosus GG, LGG) and gram‐negative ( Escherichia coli Nissle 1917, EcN) probiotics is lacking. By activating the DC‐IL‐12‐NK immune axis, EcN colonization of neonatal gnotobiotic pigs mediates greater protection against human rotavirus than LGG. Abstract : Lactobacillus rhamnosus GG (LGG), a gram‐positive lactic acid bacterium, is one of the most widely used probiotics; while fewer gram‐negative probiotics including Escherichia coli Nissle 1917 (EcN) are characterized. A mechanistic understanding of their individual and interactive effects on human rotavirus (HRV) and immunity is lacking. In this study, noncolonized, EcN‐, LGG‐, and EcN + LGG‐colonized neonatal gnotobiotic (Gn) pigs were challenged with HRV. EcN colonization is associated with a greater protection against HRV, and induces the highest frequencies of plasmacytoid dendritic cells (pDCs), significantly increased NK‐cell function and decreased frequencies of apoptotic and TLR4 + mononuclear cells (MNCs). Consistent with the highest NK‐cell activity, splenic CD172 + MNCs (DC enriched fraction) of EcN‐colonized pigs produced the highest levels of IL‐12 in vitro. LGG colonization has little effect on the above parameters, which are intermediate in EcN + LGG‐colonized pigs, suggesting that probiotics modulate each other's effects. Additionally, in vitro EcN‐treated splenic or intestinal MNCs produce higher levels of innate, immunoregulatory and immunostimulatory cytokines, IFN‐α, IL‐12, and IL‐10, compared to MNCs of pigs treated with LGG. These results indicate that the EcN‐mediated greater protection against HRV is associated with potent stimulation of the innate immune system and activation of the DC‐IL‐12‐NK immune axis.